Effectiveness of an Application-Based Health Promotion Program on Prenatal Yoga for Pregnant Women - Sandra Tombokan; Atik Purwandari; Sjenny Tuju (Poltekkes Kemenkes Palu, 2025)
Background: Sleep disturbances are reported by approximately 78% of pregnant women in the United States, a figure significantly higher than in the pre-pregnancy period. Fatigue is a common complaint among expectant mothers, particularly during the third trimester. On average, pregnant women wake up between 3 to 11 times each night, with less than 2% experiencing uninterrupted sleep. In Indonesia, the prevalence of sleep disorders among pregnant women reaches about 64%. Furthermore, 65% of pregnant women with sleep apnea tend to deliver via cesarean section, and around 42% develop preeclampsia. This study aimed to evaluate the effectiveness of health promotion through prenatal yoga delivered via a web-based application for pregnant women. Method: A quasi-experimental method was used, employing a one-group pre-test and post-test design. The study took place in the working area of Amurang Health Center, South Minahasa Regency, from April to September 2023, involving 35 pregnant women in their third trimester. The participants were selected using accidental sampling. Data were collected through direct observation using a knowledge questionnaire (3 items) and the Pittsburgh Sleep Quality Index (PSQI) questionnaire (7 components). Data were analyzed using univariate and bivariate methods, with the Wilcoxon Signed Rank Test applied for statistical testing. Results: The findings indicated a significant improvement in sleep quality among third-trimester pregnant women after participating in the prenatal yoga sessions via the web application (P-value<0.001 < 0.05). Conclusion: The promotion of prenatal yoga through a web-based platform is effective in enhancing sleep quality in third-trimester pregnant women. It is recommended that pregnant women continue practicing prenatal yoga at home twice every two weeks using the application.